Optimization of Sperm Cryopreservation Protocol for Peregrine Falcon (Falco peregrinus) - Beatriz Cardoso; Irene Sánchez-Ajofrín; Cristina Castaño; Olga García-Álvarez; Milagros Cristina Esteso; Alejandro Maroto-Morales; María Iniesta-Cuerda; José Julián Garde; Julián Santiago-Moreno; Ana Josefa Soler (Animals, 2020)
Sperm cryopreservation is a complex process that needs to be adapted to wild and domestic avian species to ensure proper efficiency. Because of its accessibility, the peregrine falcon may be used as a good model for studying other raptor species. To find the most optimal cryopreservation protocol for peregrine falcon ejaculates, sperm parameters such as motility, viability, DNA fragmentation, acrosome integrity, and mitochondrial activity were analyzed under different conditions by varying the freezing method (slow freezing in straws vs. ultrarapid freezing in pellets), thawing conditions (37 °C for 30 s vs. 5 °C for 1 min), type of cryoprotectant (DMA vs. DMSO), and concentration of DMSO (4% vs. 8%). Results show that slow cryopreservation in straws yielded greater percentages (p < 0.05) of motile spermatozoa (22.5% ± 4.4% vs. 0.0% ± 4.1%), viable spermatozoa with intact acrosomes (84.6% ± 4.3% vs. 77.4% ± 4.3%), and spermatozoa with active mitochondria (41.0% ± 6.7% vs.12.8% ± 6.7%), compared with those obtained by the ultrarapid freezing in pellets. However, no differences were found between different thawing conditions. Moreover, all sperm motility parameters were greater (p < 0.05) when DMSO was used during freezing compared with DMA, although the use of 3% and 8% DMSO produced similar results. In conclusion, these results represent important progress in the study of falcon semen cryopreservation protocol, highlighting the crucial steps of the process and the most suitable conditions.